An Analysis of Code-Mixing Used by Boy William on Vlog #Dibalikpintu - Dwi Handayani; Ricky Eka Sanjaya (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The research aims to describe and to analyze the forms of code-mixing used by Boy William on Vlog #Dibalikpintu. This study was a descriptive qualitative method and human research is the main instrument of this study. In collecting the data, this study utilized observation and documentation methods. This study employed content analysis which focused on analyzing the forms of code-mixing which were defined by Suwito (1983). The result of this study: In the word form, there are 19 data found, (15 nouns, 2 verbs, 1 adjective, 1 question word). In the phrase form, there are 19 data found, (17 noun phrases, 2 adjective phrases). In the baster form, there are 5 data found, (1 noun as a form of gerund suffixation, 3 noun suffixation, 1 verb suffixation). In the word reduplication form, there are 2 data found, (1 noun, 1 compound noun). In the idiom form, there are 2 data found, (1 formal idiom, 1 informal idiom). In the clause form, there are 25 data found, (8 noun clauses, 14 verb clauses, 3 adjective clauses).